Ladies' Greek : Ladies` Greek - Prins, Yopie (Princeton University Press, 2017)
Cover -- Title -- Copyright -- Dedication -- CONTENTS -- List of Illustrations -- PREFACE -- Between Alpha and Omega -- Acknowledgments -- INTRODUCTION: WOMEN AND THE GREEK ALPHABET -- An Ode in Greek -- "Some Greek upon the Margin" -- "Ought Women to Learn the Alphabet?" -- Translating Greek Tragedy -- CHAPTER ONE: THE SPELL OF GREEK -- Virginia Woolf's Agamemnon Notebook -- Cassandra between the Stage and the Page -- OTOTOTOI -- CHAPTER TWO: ΙΩ IN PROMETHEUS BOUND -- "So Harsh a Chain of Suffering" -- Greek Verbs in Me -- "A Goodly Company of Lady-Translators" -- The Flight of Io, to America and Back to Greece -- CHAPTER THREE: THE EDUCATION OF ELECTRA -- Behold and See -- Electra at Girton College -- Electra at Smith College -- CHAPTER FOUR: HIPPOLYTUS IN LADIES' GREEK (WITH THE ACCENTS) -- New Measures for New Women -- "A Brisk Interchange of Letters" -- Euripidean (De)Cadence -- H.D.'s Euripides: Feet, Feet, Feet, Feet -- CHAPTER FIVE: DANCING GREEK LETTERS -- Modern Maenads -- Jane Harrison's Thrill -- Bryn Mawr College Rituals -- POSTFACE -- Reading the Surface -- Refractions of Antigone -- How to Read Ladies' Greek -- Notes -- Bibliography -- Index.